Pengaruh Artificial Intelligence dan Social Media Marketing terhadap Minat Beli Generasi Z - Kusnara, Hasti Pramesti; Pirous, Haekal; Fajri, Fallah Jihadil Fajri (Ma'soem University, 2025)
The development of digital technology has encouraged companies to innovate in marketing strategies, especially through the use of Artificial Intelligence (AI) and social media. Generation Z, as the largest and most active digital users in Indonesia, including in Sumedang Regency, has unique characteristics in consumer behavior. This study examines the impact of Artificial Intelligence and social media marketing on the purchase intention of consumers, specifically targeting Generation Z in Sumedang Regency. The findings reveal that the simultaneous application of AI (utilized for data analysis, content personalization, chatbots, and trend prediction) and social media marketing (employed for consumer outreach and interaction) yields a positive and significant effect on their willingness to buy. Data gathered from 100 Gen Z respondents through an online questionnaire were analyzed using the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS). The analysis produced a strong R-Square value of 0.915, proving the model's high accuracy in explaining the variables that influence consumer purchase intention. Consequently, this research concludes that incorporating AI into social media marketing strategies is an effective way to boost purchase intention among the Gen Z demographic.